Os daguerreótipos e a ideia de Alemanha: modelos iconográficos e representações sociais na região alemã de 1839 a 1871 - Callado, Vanessa Freitas Mendes (2023)
This thesis aims to comprehend the use of the daguerreotype in the German regions, from the moment in which the technique was patented, in 1839, until the year of the unification of the states that would eventually become Germany, in 1871. The objective of the thesis is to understand how the technique was used in this period, and if the daguerreotype contributed to the dissemination of the national unification project. The region of Germany was chosen as the daguerreotype was enthusiastically adopted by its practitioners and by the professional studios industry. Amongst a considerable number of studios, the following photographers are spotlighted in this thesis: Hermann Biow, Carl Ferdinand Stelzner, Bertha Wehnert-Beckmann, Phillip Graff e Hermann Krone. The use of daguerreotypes for portraits remained being predominantly used in the studied region until the decade of 1860, in a time it was already not so commonly used by its neighboring countries. The region was also chosen given that one of its most historic moments – the unification of the country – coincided with the period of largest use of the technique. The growing nationalism made the daguerreotype one of its instruments. On top of that, the future Germany possessed a strong tradition for graphic arts, which had close ties with the daguerreotype. One of the aspects evidenced during this thesis was the intensive link between the daguerreotype with other types of art, mainly graphic arts. We understood, from analyzing the images of the lithographs from the 1848 deputies of the Constitution Chamber, which were made using daguerreotypes, that the engraving could make possible the reproducibility of the daguerreotypes, which are unique pieces. Daguerreotypes did not supplant other traditional techniques, which were often preferred. The models, poses, and objects used in daguerreotype portraits follows an iconography that was not invented alongside the photography, but reproduced from the earlier iconographic models in paintings, drawings, and engravements. Because of this movement of iconographic exchanges, it is evidenced that photography was one of the possibilities of the art system in the 19th century. This thesis makes use of iconographic comparisons from research in collections, having selected a large database to identify representation models. We came to understand that, both on political and familiar spectrums, the use of the daguerreotype in the region indicated a social function